The role of gallic acid in liver disease: a review of its phytochemistry, pharmacology, and safety - Li, Peiyu; Song, Yifan; Lv, Linlin; Zhang, Wenshuo; Jia, Aixi; Dong, Deshi; Zhai, Xiaohan (Frontiers in Pharmacology, 2025)
BackgroundThe development of liver diseases adversely affects global health, emerging as a prominent cause of mortality globally and imposing a significant economic strain on society. Gallic acid (GA) is the natural polyphenol that is present in a variety of plants, fruits, tea, traditional Chinese medicine and so on.PurposeThis review was aimed to analyze the available literature on GA with a focus on its mechanism of action.MethodsSeveral literature databases were searched, including PubMed, Web of Science, Google Scholar, and Scopus to find relevant research on GA and liver disease over the last decade.ResultsOur finding indicate that GA can effectively reduce non-alcoholic liver injury, alcoholic liver disease, hepatic fibrosis, drug-induced liver injury, and liver cancer. GA displays remarkable antioxidant effects by activating nuclear factor erythroid 2-related factor (Nrf2) and the expression of antioxidant genes. Moreover, the anti-inflammatory mechanism is mainly related to the nuclear factor kappa B (NF-κB) signaling pathway and down-regulating some inflammation-related factors such as interleukin 1 (IL-1), interleukin 6 (IL-6), transforming growth factor-beta (TGF-β) and tumor necrosis factor alpha (TNF-α). GA mitigates non-alcoholic fatty liver disease (NAFLD) and alcoholic liver disease (ALD) through the reduction of lipid accumulation, achieved by modulating the AMP-activated protein kinase (AMPK) signaling pathway. In the context of liver cancer, GA additionally modulates the wnt/β-catenin and JAK/STAT3 signaling pathways, as well as their downstream molecular components.ConclusionIn this review, different studies indicate that GA have an excellent protective effect against various liver diseases associated with various signaling pathways.